(untitled) (Docentes 2.0 Journal, 2024)
Artificial Intelligence (AI) is presented as a useful tool if used as an instrument of innovation, freeing up time and resources for creativity, a human condition that should not be automated. The research aimed to demonstrate that AI, providing tools, resources, and data analysis, can foster and support human creativity. The research was based on a systematic method with a phenomenological humanistic paradigm, a qualitative approach, and a topical narrative design. The study was classified as an exploratory and cross-sectional documentary. A total of 10 articles obtained from the Eric, Scopus, and WOS databases were analyzed, with a maximum age of five years. Documents irrelevant to the central topic were discarded. The findings revealed the technological advancement in AI between 2019 and 2020, highlighting its application in fields such as medical sciences, design, audiovisual language, and photography. The review used thematic content analysis and showed that AI has great potential to enhance human creativity. It also underlined the importance of the qualitative approach in recent studies and the need to synthesize information for future research. It concluded that AI could enhance human creativity by providing tools and resources that facilitate artists and creative professionals, optimize repetitive tasks, and offer real-time data analysis.